Iras oxygen- and carbon-rich miras close to the galactic plane - Leeuw, Lerothodi La Pula (Department of Astronomy, 2016)
Observations are presented for 101 I RAS sources that were expected to be Mira Variables and that lie close to the galactic plane: -7.0 3 < b < + 1° and 282.°5 < l < 285.°5. Over 1090 JHKL photometry modules were obtained for the sources. From the photometry the sample was shown to comprise 85 Miras, 12 of which had published periods. New periods were determined for all the Miras. Of the 85 Miras in the sample, 21 had previous published spectra and the rest were tentatively classified as oxygen or carbon-rich Miras using infrared two-colour diagrams. The oxygen and carbon-rich Miras, respectively, have mean periods and K half-amplitudes of 386 days and 0.36 mag and 442 days and 0.46 mag. Statistical tests showed that the probability that the period distribution functions of the oxygen and carbon-rich stars came from the same population was very small: 0.00055. The period as well as the K- Land K- [12μm] colours were shown to be functions of amplitude. For the carbon-rich Miras the [12μm]- [25μm] colour was shown to be correlated with amplitude. Bolometric magnitudes were determined by integrating under a spline curve fitted to the J H K L12, 25μm fluxes of the Miras. Distances to the stars have been calculated using absolute magnitude P- L relations from oxygen-rich and carbon-rich Miras in the LMC, where the LMC distance modulus of 18.57 was adopted. In addition, a search of Miras in the Galactic Bulge using APM-scanned !-plate data are presented. A total of 116 Mira candidates were identified, 43 of which were classified as strong candidates. The presented work will contribute to the study of Galactic structure.